Astragaloside IV attenuates inflammatory injury and promotes odontoblastic differentiation in lipopolysaccharide‐stimulated MDPC‐23 cells and rat pulpitis. (19th August 2019) - Ding, Qun; Gao, Jinyu; Zheng, Jing; Wang, An; Jing, Shuanrang
Abstract: Background: Astragaloside IV (AS‐IV), a natural herbal compound from Astragalus membranaceus, has inhibitory effects on receptor activator of nuclear factor‐κB ligand (RANKL)‐induced osteoclastogenesis, and RANKL signal helps to regulate odontoblast differentiation. However, whether and how AS‐IV affects odontoblastic differentiation remains unclear. Methods: Lipopolysaccharide (LPS)‐stimulated MDPC‐23 cells and rat pulpitis were treated with AS‐IV, cell viability, and LDH leakage was analyzed by CCK‐8 assay and LDH Leakage assay. The production of TNF‐α and IL‐6 was determined by ELISA and qRT‐PCR assay. The expression of alkaline phosphatase (ALP) was detected using an ALP assay kit, and the expression of dentin sialophos‐phoprotein (DSPP), dentin matrix protein‐1 (DMP1), basic fibroblast growth factor (FGF2), and phosphorylated extracellular signal‐regulated kinase (p‐ERK) was determined by western blot. Results: AS‐IV dose dependently increased in cell viability and decreased the overproduction of TNF‐α and IL‐6 in LPS‐stimulated MDPC‐23 cells. AS‐IV also counteracted LPS‐induced downregulation of ALP, DSPP, and DMP1 in MDPC‐23 cells. Furthermore, AS‐IV significantly decreased the expression of FGF2 and p‐ERK in LPS‐stimulated MDPC‐23 cells. More important, the addition of FGF2 partly neutralized AS‐IV‐mediated inhibition of FGF2/ERK signaling, abolished AS‐IV‐induced reduction of TNF‐α and IL‐6, and counteracted AS‐IV‐induced upregulation of DSPP and DMP‐1 in these cells. Meanwhile, AS‐IV inhibited the excessive production of TNF‐α and IL‐6, suppressed the downregulation of DSPP and DMP1, and disturbed the up‐regulation of FGF2 and p‐ERK in the pulp tissues of rat pulpitis model. Conclusions: AS‐IV exerted anti‐inflammatory and pro‐differentiation effects in LPS‐stimulated MDPC‐23 cells and rat pulpitis via inhibiting the FGF2/ERK signaling pathway.